The Unusual Late-Onset Graves’ Disease following Hashimoto’s Related Hypothyroidism: A Case Report and Literature Review - Aseel Sukik; Sara Mohamed; Mhd-Baraa Habib; Sundus Sardar; Bashar Tanous; Raad Tahtouh; Mouhand F. H. Mohamed (Case Reports in Endocrinology)
Background. The shift of Graves’ disease (GD) to Hashimoto’s disease- (HD-) related hypothyroidism is well established. However, the opposite is rare. This is likely to the loss of critical thyroid mass available for stimulation by thyroid hormone receptor stimulating antibody, making this shift unusual. Herein, we report a young lady with a late shift from HD into GD and present a scoping literature review. Case presentation. We report a twenty-five-year-old lady with a sixteen-year-history of Hashimoto’s-related hypothyroidism stable on levothyroxine. While following in the clinic, she started developing thyrotoxic symptoms in the form of anxiety, weight loss, and palpitation. Physical examination was remarkable for mild exophthalmos. The thyroid function test confirmed hyperthyroidism. Levothyroxine-induced hyperthyroidism was initially suspected; however, the symptoms did not improve despite reducing and stopping levothyroxine. Subsequent workup confirmed the diagnosis of GD. Discussion and Conclusion. This case highlights a unique association that has significant diagnostic and management implications. This shift should be considered when hyperthyroidism persists despite reducing or stopping levothyroxine. The diagnosis is made utilizing antibody titers and radioiodine update scan. While the management depends on the disease’s stage and the treating physician preference, antithyroid agents can be used initially. Following up these patients is essential as the shift can be transient.